The impact of behavioural skills training on the knowledge, skills and well‐being of front line staff in the intellectual disability sector: a clustered randomised control trial. - Gormley, L.; Healy, O.; O'Sullivan, B.; O'Regan, D.; Grey, I.; Bracken, M. (Journal of Intellectual Disability Research, 2019)
Background: Staff with varying backgrounds and educational qualifications can be effectively trained to implement procedures in line with evidence‐based practice. Behavioural skills training (BST) is a competency‐based training model used to effectively educate a broad selection of professionals, including front line staff, in a range of work‐related skills. However, BST has yet to be evaluated in a large group‐based experiment. Methods: This study involved a parallel cluster randomised control trial. Six service sites, with a total of 54 participants, were randomised to the intervention condition using the 'coin toss' method. The intervention condition used BST to coach intellectual disability staff in reinforcement, systematic prompting, functional communication training and task analysis. Six service sites, with a total of 50 participants, were also randomised to a control condition in which generalised training in behavioural interventions was restricted. Recruited service sites were randomly assigned to the intervention condition (N = 6, n = 54) or the control condition (N = 6, n = 50) at one point in time, immediately after recruitment and before baseline testing took place. Allocations were stratified by service type (residential or day) and geographical region. One member of the research team allocated service sites using the 'coin toss' method, and another member, blind to the allocations, decided which experimental arm would receive the intervention and which would be designated as control. It was not possible to mask the intervention from participants, but they were recruited prior to randomisation. Results: Participants in the intervention condition demonstrated statistically significant improvements in their knowledge scores over the study period. Participants in the control condition showed no change or a statistically significant decrease in their knowledge scores. No statistically significant changes to well‐being were observed for either group. There was clear evidence of knowledge maintenance, as well as skill acquisition and subsequent generalisation to the workplace environment, among participants in the intervention condition. Participants also evaluated the BST intervention positively. Conclusions: Results support BST as a method for disseminating evidence‐based practice to front line staff working with adults with intellectual and developmental disabilities.